Role of CR1 Knops polymorphism in the pathophysiology of malaria: Indian scenario - Monika Gandhi, Arpita Singh, Vas Dev, T. Adak, A.P. Dash & Hema Joshi (Journal of Vector Borne Diseases, 2009)
Background & objectives: Plasmodium falciparum is the leading cause of mortality and causescerebral malaria associated with sequestration caused by cytoadherence of the trophozoite andschizont-infected erythrocytes to the endothelial cells of the deep vascular beds in the brain.Pathophysiology of malaria is complicated by rosetting. Rosetting is a process of binding ofuninfected erythrocytes to the erythrocytes infected with mature asexual parasites and is controlledby expression of complement receptor 1 (CR1) on RBC surface. Various polymorphic forms ofCR1 are known including molecular weight polymorphism, red blood cell expression levels/densitypolymorphism and Knops (KN) polymorphism. The Knops blood group includes several allelicpairs; Knops a and b (Kna and Knb), McCoy a and b (McCa, McCb), Swain-Langley (Sla), andVillien (Vil). Knops phenotype Sl (a–) has been found to rosette less effectively than Sl (a+) andhence suggested to be more protective. P. falciparum cases have not reduced much as compared tothe reduction in the total number of malaria cases in the past few years. In addition, P. falciparumis the leading cause for all mortality and most of the morbidity in India. We, therefore, investigatedthe role of CR1 Knops polymorphism in the pathophysiology of malaria in Indian population.Methods: A case control approach was used for this study. CAPS (Cleaved amplified polymorphicsequence) methodology was adopted. A total of 100 normal individuals (free from any ailment)and 100 individuals suffering from P. falciparum infection (uncomplicated malaria) were recruitedfor this study.Results: We found that in Indian population (normal individuals and P. falciparum-infectedindividuals), only the wild type allele is present.Interpretation & conclusion: We concluded that the process of rosetting in the Indian contextcould be occurring independently of the effect of Knops polymorphism and in part could be controlledby other polymorphisms of the CR1 gene (density and structural polymorphism).